2011
DOI: 10.1016/j.atmosres.2010.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-to-ground lightning and Mesoscale Convective Systems

Abstract: This work analyzes some of the physical and microphysical properties of Mesoscale Convective Systems (MCS) and cloud-to-ground lightning. Satellite data from the GOES-10 infrared and NOAA-18 and TRMM microwave channels and lightning information from the Brazilian Lightning Detection Network (BrasilDAT) were utilized for the period from 2007 to 2009. Based on an automatic MCS detection method, 720 MCS life cycles were identified during the period and region of study, with a lightning detection efficiency of ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 87 publications
1
18
0
8
Order By: Relevance
“…mountain height), and shows strong seasonal and diurnal patterns related to the timing of the most intense convective storms (Rivas Soriano et al, 2005;Mattos and Machado, 2011). This is clearly seen in Figure 3b, where the relationship between the total (2000-2010) CG flash density and altitude is shown.…”
Section: Resultsmentioning
confidence: 79%
“…mountain height), and shows strong seasonal and diurnal patterns related to the timing of the most intense convective storms (Rivas Soriano et al, 2005;Mattos and Machado, 2011). This is clearly seen in Figure 3b, where the relationship between the total (2000-2010) CG flash density and altitude is shown.…”
Section: Resultsmentioning
confidence: 79%
“…The authors documented that many of the flashes observed in thundersnow were associated with localized high‐ Z H and low‐ Z DR regions, suggesting regions with graupel production indicating that storms with lightning could have larger and more numerous graupel content than storms without lightning. Observations from ground‐based total lightning combined with Doppler and polarimetric radar [ Deierling and Petersen , ], numerical simulations with explicit microphysics [ Calhoun et al ., ], and satellite observations [ Mattos and Machado , ; Matthee and Mecikalski , ] also support this idea, and it is suggested that storms with lightning include better graupel growth conditions due the existence of stronger updrafts, higher supercooled water content, and ice particle mass.…”
Section: Resultsmentioning
confidence: 98%
“…This new methodology is based on the IWP and D e results from the previous section, cloud life cycle characteristics (inferred with microwave frequencies), and recent studies related to lightning in thunderstorms. Mattos and Machado (2011) found that for D e larger than 1.2 mm (also inferred with the MSPPS algorithm), the lightning probability is higher than for smaller particles. Consequently, greater convection is observed.…”
Section: B Mspps Rain Rate Estimate Analysismentioning
confidence: 93%